ByzRev 06.2024.038: Oliver Hellmann – Arnaud Zucker (éds.), On the Diffusion of Zoological Knowledge in Late Antiquity and the Byzantine Period: (AKAN-Einzelschriften 14). Trier: WVT Wissenschaftlicher Verlag Trier 2023. - Lazaris, Stavros (The Byzantine Review, 2024)
Oliver Hellmann – Arnaud Zucker (éds.), On the Diffusion of Zoological Knowledge in Late Antiquity and the Byzantine Period (AKAN-Einzelschriften 14). Trier: WVT Wissenschaftlicher Verlag Trier 2023. 198 p. – ISBN 978-3-86821-982-1